Punduhan ng mga dumagat sa San Isidro reviving the dumagat's cultural heritage through a regenerative mixed-use agritourism hub - Calibuso, Dean Darwin B. (College of Architecture, University of the Philippines Diliman, 2025)
In 21st-century Philippine architecture, there has been a shift from urban redevelopment to the revitalization of rural areas, aiming to address challenges like underemployment, environmental conservation, and cultural heritage preservation. Within this context, the Dumagat community in the rural uplands of San Jose del Monte, Bulacan, faces significant threats from urbanization and illegal logging in the area which disrupts their traditional lifestyle and weakens their deep ties to cultural heritage and the natural environment. These challenges threaten the community's cultural integrity, creating an urgent need for holistic cultural revival. This study explores how architecture can aid in reviving the Dumagat culture by proposing aregenerative agritourism hub in Barangay San Isidro. The hub will include an eco-museum, a farm-to-table restaurant, and an agricultural farmstead designed to provide a space where Dumagat culture can thrive while educating tourists and visitors. The design focuses on the regenerative potential of agritourism, aiming to establish a strong sense of place through symbolic interactionism and architectural storytelling. Pertinent to this is the “Old and New Symbiosis” concept or the creation of a harmonious coexistence between traditional and contemporary elements which are identified in this study using cultural and landscape gene extraction methods. The findings underscore the need to integrate Dumagat cultural elements—both tangible and intangible—into modern technologies to support the survival and evolution of their cultural heritage. The design features spatial strategies that foster interaction not only between people, Dumagat community members and tourists, but also between people, nature, and the built environment. Thus, this project envisions a regenerative, interactive, and culturally immersive agritourism complex that connects visitors, locals, and the Dumagat community to the richness of Dumagat heritage